h - Cao, Zhenfu; Zhang, Fangguo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 6th International Conference on Pairing-Based Cryptography, Pairing 2013, held in Beijing, China, in November 2013. The 14 full papers presented were carefully reviewed and selected from 59 submissions. As in previous years, the focus of Pairing 2013 is on all aspects of pairing-based cryptography, including: cryptographic primitives and protocols, mathematical foundations, software and hardware implementation, as well as applied security.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Coding theory; Information theory; Computer Science; Data Encryption; Systems and Data Security; Coding and Information Theory; Theory of Computation